Evaluasi Penyebab Cacat Lahir Berdasarkan Jenis Kelamin di Sumatra Selatan, Indonesia - Michael, Michael; Ramatillah, Diana Laila; Dinli, Dwi Yunisa; Kezia, Valerie; Sutardi, Azzahrotul Qona'ah Ibnatus (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: Birth defects are inherited physical or genetic conditions that cause health complications and significant developmental delays such as intellectual functioning and adaptive behavior. The purpose of this study was to look at the types of disability, disability categories and causes of disability in boys and girls. Cross-sectional is the method used in this study. The sampling technique used in this study was convenience sampling by distributing questionnaires to parents who were willing to become respondents at special schools in South Sumatra. The results of this study involved a total of 96 respondents with 53 male and 43 female. There was no significant difference in the type of disability (0.49) suffered by boys and girls, no correlation was found between the severity of disability (0.91) and gender and there was no significant difference in the causes of disability (0.35) between boys and girls. men and women. Intellectual disability (62.5%) and mild disability (54.2%) were the most common disabilities. The main cause of disability is a deficiency of folic acid and multivitamins during pregnancy, which is 49%.